Framing of Drone Attacks in Pakistani Elite Press: A Comparative Study of Dawn and the Nation - Paracha, Sajjad Ahmed; Imran, Fatima; Khan, Muhammad Ashraf (Richtmann Publishing, 2012)
This study is a test of â€œmedia framing theoryâ€, which asserts that there is some cognitive structure lies in mind, whichleads the perception of anyone. These frames are created intentionally and sometimes, the reader himself makes them.Pakistan is at stake after 9/11 and is continuously trying to explain before the world as well as before the people of Pakistan thatshe doesnâ€™t have any link with Al-Qaeda and terrorism. To make the world believe her position, Pakistan had to become the allyin war on terror but still the people of Pakistan are facing much destruction in the shape of drone attacks. Being in such crucialposition, Pakistani media frame these air strikes negatively. This study is a semantic and narrative analysis of the editorials ofThe Nation and Dawn. A total number of 82 editorials were analyzed, 65(79.26%)of daily The Nation while 17 (20.73%)editorialsof daily Dawn. The results prove the H1, which describe that The Nation frame drone attacks more negative than Dawn.